Driving Business Performance in Jakarta’s Fried Chicken MSMEs: The Role of Product and Service Innovation in Creating Competitive Advantage - Fadhillah, Anindita; Saparuddin Mukhtar; Osly Usman (Journal of Strategic Innovation in Economics and Business, 2025)
This study investigates the strategic pathways through which product quality and service quality drive business performance in Jakarta's fried chicken micro, small, and medium enterprises (MSMEs), with competitive advantage as a mediating variable. Using a quantitative approach with structural equation modeling based on partial least squares (SEM-PLS) analysis of 101 MSME owners, the research empirically validates the Resource-Based View (RBV) theory in the emerging market context. Findings reveal that both product quality (path coefficient = 0.456 to competitive advantage) and service quality (path coefficient = 0.536 to competitive advantage) significantly enhance competitive advantage, which subsequently amplifies business performance. Service quality demonstrates the strongest direct effect on business performance (path coefficient = 0.425), while competitive advantage partially mediates the relationships between quality dimensions and performance. The exceptional explanatory power of the structural model (R² = 0.992 for business performance) confirms that quality-based competition strategies yield superior performance outcomes compared to price-based approaches in the post-pandemic culinary market. These findings demonstrate that resource-constrained MSMEs can achieve sustainable competitive advantages through strategically leveraging difficult-to-imitate quality capabilities and emotional service connections, extending RBV theory's applicability to emerging market MSME contexts and providing actionable implications for MSME strategic management and policymakers.